The relationship between the weight of the placenta and birth weight of the neonate in a Nigerian Hospital - Panti, Abubakar A. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: There have been several publications from different countries on the relationship between the placental weight and birth weight of the neonate. However, such reports from Nigeria are lacking in literature. The objective of this study was to determine the relationship between the placental weight and birth weight of the neonate at term pregnancy in a Nigerian hospital. MATERIALS AND METHODS: It was a cross-sectional study conducted at Usmanu Danfodiyo University Teaching Hospital Sokoto between 1(st) October 2008 and 31(st) March 2009. Data gestational age at delivery (in weeks), parity, mode of delivery, fetal birth weight, placental weight, fetal gender, presence or absence of maternal medical diseases were obtained from 1009 singleton term deliveries who met the inclusion criteria for the study. The data was processed using EPI-INFO version 2005 and statistical analysis performed using one-way analysis of variance. A probability of 0.05 was set for statistical significance. RESULTS: The placental birth weight ranged from 300 to 890 g with a mean of 590±82 g while the birth weight of the neonate ranged from 2030 to 5020 g with an average of 3275±469 g. The mean gestational age at delivery was 38.8±1.1 weeks while the mean placental birth weight ratio was 18.2±2.4 Increase in birth weight of the neonate was associated with corresponding increase in placental weight. However, as the gestational age at term advances the proportion of increase in the former was greater than that of the latter. CONCLUSIONS: There is a positive correlation between placental weight and birth weight of the neonate. However, the ratio of the placental and neonatal birth weights at term decreases with advancing gestational age. Thus, prolongation of pregnancy at term may adversely affect the fetus.